The product of the hypB gene, which is required for nickel incorporation into hydrogenases, is a novel guanine nucleotide-binding protein. - Maier, T (1993)
The products of the hyp operon genes are essential for the formation of catalytically active hydrogenases in Escherichia coli. At least one of these auxiliary proteins, HYPB, appears to be involved in nickel liganding to the hydrogenase apoprotein, since mutations in hypB can be phenotypically suppressed by high nickel concentrations in the medium (R. Waugh and D. H. Boxer, Biochimie 68:157-166, 1986). To approach the identification of the specific function of HYPB, we overexpressed the hypB gene and purified and characterized the gene product. HYPB is a homodimer of 31.6-kDa subunits, and it binds guanine nucleotides, with a Kd for GDP of 1.2 microM. The protein displays a low level of GTPase activity, with a kcat of 0.17 min-1. The apparent Km for GTP, as measured in the GTP hydrolysis reaction, was determined to be 4 microM. A chromatography system was established to measure nickel insertion into hydrogenase 3 from E. coli and to determine the effects of lesions in hypB. Nickel appears to be associated only with the processed large subunit of hydrogenase 3 in the wild type, and hypB mutants accumulate the precursor form of this subunit, which is devoid of nickel. The results are discussed in terms of a model in which HYPB is involved in nickel donation to the hydrogenase apoprotein and in which GTP hydrolysis is thought to reverse the interaction between either HYPB or another nickel-binding protein and the hydrogenase apoprotein after the nickel has been released.